1990
DOI: 10.1007/bf02336568
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality evoked potentials in HIV infected subjects: A longitudinal study

Abstract: 18 subjects with symptomless HIV infection were investigated with multimodal evoked potentials for possible CNS involvement and again after an 8-12 month interval. 13 subjects showed neuropsychological changes, which were confirmed at the second examination. The 5 subjects found normal remained so at the second examination. On WAIS assessment the only patient to earn pathological scores was the one with the greatest evoked potentials changes. Thus the evoked potentials procedure proved capable of identifying e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Similarly, Koralnik et al (1990) and Cazzullo et al (1990) reported slowed somatosensory ERPs in relatively healthy (asymptomatic) HIV patients.…”
Section: Purposementioning
confidence: 76%
“…Similarly, Koralnik et al (1990) and Cazzullo et al (1990) reported slowed somatosensory ERPs in relatively healthy (asymptomatic) HIV patients.…”
Section: Purposementioning
confidence: 76%